Musica Studio's Corporate Communication Strategy In The Digital Era (Case Study On Musica Studio's Managing Noah's Band Existence) - Fatmawati, Yeni; Wahid, Umaimah; Sigit, Ridzki Rinanto; Ariyani, Nafiah; Mulyasantosa, Nandang (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study analyzes Musica Studio's corporate communication strategy in maintaining Noah's existence in the digital era by using the post-positivism paradigm, qualitative approach, and case study methods. The results of the study show that digital transformation encourages Musica Studio's to integrate communication strategies, crisis management, and digital marketing through the Omni Marketing 12C framework. This approach puts the community at the center of segmentation and target markets, strengthens Noah's positioning and differentiation through consistency of brand identity and narrative, and creates new value based on collaboration and digital experiences. The implementation of digital marketing through websites, social media, streaming services, and virtual concerts allows for strengthening relationships with audiences and optimizing new revenue models. In addition, co-creation, communal activation, and conversational promotion form a participatory and adaptive communication ecosystem. Overall, Musica Studio's strategy shows that brand sustainability and crisis management effectiveness in the modern music industry depend on the integration of technology, community, and collaboration as the foundation of corporate communication in the digital age.